RETURN PROBLEMS OF GRAVIMETRY AND MAGNETIC WITH USE OF DERIVATIVES OF DISCRETELY SET FIELD AND THEM CERTAINLY-DIFFERENT FORMULAS - Minenko, P.; Minenko, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The problem is considered and borders of reliable calculation of derivatives of discretely set field are established. Corresponding methodical receptions, theoretical methods and practical recommendations which improve quality of the decision of return problems gravimetr and magnetic, including, with use certainly-different formulas for the measured and theoretical field are developed.